Evolution of publishing production in the Autonomous Community of Extremadura, Spain (2007-2015) - Soto-Vázquez, José; Jaraíz-Cabanillas, Francisco Javier; Gutiérrez-Gallego, José Antonio; Pérez-Parejo, Ramón; Tena Fernández, Ramón (Revista General de Información y Documentación, 2019)
This study analyzes the evolution of publishing production in the Autonomous Community of Extremadura (Spain) in the period 2007-2015, that is, at a stage of serious global economic crisis. After presenting the objectives and hypothesis, the editorial data are shown making comparisons between Spain and Extremadura and paying special attention to variables such as the type of support and the nature of the editorial agents. As more important conclusions, the economic crisis produces serious alterations in the editorial sector of the region; from 2007 to 2010 the production continues to grow, but from then until 2016 it gradually decreases; there are more companies and more books are published in the province of Badajoz; the production of electronic books in Extremadura is very low; with the economic crisis the number of private publishing companies increased and the institutional ones reduced their weight; the intervention of the institutions are decisive in the dynamism of the publishing industry in the region.
Keywords: Extremadura; Editorial; Crisis; Book; Economy